2015
DOI: 10.4103/0253-7613.165185
|View full text |Cite
|
Sign up to set email alerts
|

Maxcal-C (a polyherbal formulation) prevents ovariectomy-induced osteoporosis in rats

Abstract: Objectives:The aim of the present study was to investigate the anti-osteoporotic activity of Maxcal-C in ovariectomy (OVX)-induced osteoporosis in rats.Materials and Methods:Sham-operated control rats were designated as Group I; Group II animals served as OVX control; Group III OVX control rats treated with Calcium Sandoz (50 mg/kg, p.o.); Group IV and V OVX control rats treated with Maxcal-C (250 and 500 mg/kg, p.o.), respectively. All the aforementioned treatments were given for four weeks after the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…From literature review, significant bone loss occurs from 4 to 8 weeks following ovariectomy in rats, depending on bone site examined and the technology applied. [19][20][21] It is reported that a loss of trabecular connection can be seen at 2 weeks following ovariectomy. 22 In this study, osteoporosis was induced and then a significant effect on trabecular bone was observed as early as 3 weeks after OVX surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From literature review, significant bone loss occurs from 4 to 8 weeks following ovariectomy in rats, depending on bone site examined and the technology applied. [19][20][21] It is reported that a loss of trabecular connection can be seen at 2 weeks following ovariectomy. 22 In this study, osteoporosis was induced and then a significant effect on trabecular bone was observed as early as 3 weeks after OVX surgery.…”
Section: Discussionmentioning
confidence: 99%
“…From literature review, significant bone loss occurs from 4 to 8 weeks following ovariectomy in rats, depending on bone site examined and the technology applied . It is reported that a loss of trabecular connection can be seen at 2 weeks following ovariectomy .…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is associated with severe complications, such as skeletal deformity and increased bone fractures; therefore, efficient treatments for osteoporosis are required urgently. (41) SAS promoted osteogenic differentiation of MSCs; therefore, it was used to treat our osteoporotic OVX mice. To our surprise, SAS treatment could alleviate the bone loss of OVX mice.…”
Section: Discussionmentioning
confidence: 99%